الاعتقالات السياسية واحوال المعتقلين في عصر سلاجقة العراق 513-590هـ./1120-1193 م. - اللبودي، حنان مبروك سعيد (جامعة عين شمس - كلية الآداب, 2019)
يعد موضوع الاعتقالات السياسية وأحوال المعتقلين في عصر سلاجقة العراق (513: 590ه/ 1119: 1194م)، من الموضوعات المهمة والتي تلقي الضوء على أحوال بعض الشخصيات من سلاطين وأمراء ووزراء وأصحاب بعض المناصب الإدارية الحيوية، ممن تعرضوا للاعتقال داخل دولة سلاجقة العراق. لقد كانت الأسباب السياسية هي المحرك الأول والأخير في حدوث تلك الاعتقالات، وذلك من أجل الحفاظ على المناصب التي يتولاها الشخص سواء منصب السلطنة، أو أي منصب آخر داخل البلاط السلطاني، ولقد اتبعت العديد من العديد من الوسائل والحيل والمكائد للإيقاع بالشخص وإصدار أمر باعتقاله، وتنوعت تلك القرارات فهناك قرارات صدرت من قبل السلاطين لاعتقال بعض الشخصيات داخل الدولة، وقرارات صدرت من قبل رجال الدولة من وزراء وأمراء لمن ينافسونهم في تولي المناصب، وأيضاً من قبل الأمراء والآتابك لبعض سلاطين سلاجقة العراق. حرص الشخصيات التي استصدرت أمر الاعتقال وقامت بتنفيذه على اختيار أماكن الاعتقال من قلاع وحصون منيعة، يتولى شئونها حراس أشداء. اختلفت أحوال المعتقلين بعد اعتقالهم ما بين قتلهم بالسم أو الخنق، أو أن يحرص المعتقل ويبذل في ذلك قصاري جهده على فداء نفسه بالأموال.
The subject of the political arrests and the conditions of the detainees in the era of the Seljuk's of Iraq (513: 590 AH / 1119: 1194 AD) is one of the important topics that sheds light on the conditions of some personalities from sultans, princes, ministers and holders of some vital administrative positions who were arrested inside the Seljuk state of Iraq. The political reasons were the first and last engine of these arrests, in order to maintain the positions held by the person, whether the position of the Sultanate, or any other position within the Royal Court, and has followed many of many methods and tricks and intrigues to arrest the person and issue a warrant for his arrest, These decisions are sparks issued by the sultans to arrest some figures within the state, and decisions issued by the men of the state of ministers and princes of those who compete in the office, and also by the princes and officers of some sultans of the Seljuks of Iraq. The keenness of the personalities who obtained the arrest warrant and executed it to choose places of detention from castles and impregnable fortresses, whose affairs are heavily guarded. The conditions of the detainees differed after they were arrested between killing them with poison or suffocation, or the detainee is careful and in doing so he makes every effort to redeem himself with money.
Keywords: الاعتقالات السياسية -- المسجونون السياسيون -- العصر السلجوقي -- العراق